Trophic Change and Community Decline in Acrobat Ants After Rainforest Conversion to Cash Crops - Jessica Ehlers; Tamara R. Hartke; Noah Janotta; Amanda Mawan; Rizky Nazarreta; Rizky Desriana; Purnama Hidayat; Damayanti Buchori; Stefan Scheu; Melanie M. Pollierer; Jochen Drescher (Ecology and Evolution)
ABSTRACT The conversion of tropical rainforests to agriculture causes population declines and biodiversity loss across taxa. This impacts ants (Formicidae), a crucial tropical group for ecosystem functioning. While biodiversity loss among ants is well documented, the responses of individual ant taxa and their adjustments in trophic strategies to land‐use change are little studied. Here, we investigated a collection of > 12,000 acrobat ants (Crematogaster) from 14 species collected by canopy fogging in four land‐use systems in Jambi Province, Sumatra, including (1) lowland rainforest, (2) jungle rubber (low impact rubber agroforestry), and monocultures of (3) rubber and (4) oil palm. Abundance‐weighted trophic positions as indicated by stable isotopes of carbon and nitrogen were significantly different between land uses: Lower average, maximum, minimum and range of δ13C values in monocultures than in rainforest and jungle rubber indicate a shift of Crematogaster towards more plant‐based resources, but may be driven substantially by the “canopy effect” of differential carbon assimilation of leaves between lower and higher canopy. Similar Δ15N average, maximum and minimum among the land uses, but a significantly reduced range of Δ15N in monocultures, suggest lowered trophic diversity and increased stochasticity of trophic niches in monocultures. In contrast, community decline in Crematogaster was very pronounced, with density, richness and rarity in monocultures of rubber and oil palm at a fraction of that in rainforest and jungle rubber. Crematogaster communities in oil palm formed a subset of those in rubber, which were a subset of those in jungle rubber, which were a subset of those in rainforest. A notable exception was Crematogaster ferarii, which was exclusively found in oil palm. In conclusion, tropical land‐use change induces slight shifts in the trophic structure of Crematogaster communities, but massive declines in its density and diversity. This likely affects Crematogaster‐driven ecosystem functions in agricultural systems in Southeast Asia.